Validity and reliability of three teachers’ ratings scales of socials be-haviors in preschoolers and scholars children. - Rodríguez Villagra, Odir; Padilla Mora, Michael; Fornaguera Trías, Jaime (Anales de Psicología / Annals of Psychology, 2010)
The purpose of this study was to expose validity and reliability of three teacher’s ratings scales of socials behaviors in one sample (N=262) of preschoolers and scholars (grade one) Costa Ricans children. We design one scale of prosocial behavior (ECPRO) and other to evaluate the ability of exploiter the other’s expertise (EXHAD). Moreover we adapt one scale of machiavellian behavior (EMach). Teachers completed three scales for each participant. Factor structure was evaluated by principal components analysis. This analysis show that ECPRO is form by one component “Disposition for help others”, EXHAD is constitute by two components “Social Learning by Observation” and “Exploiting the Fruits of Other’s Expertise”; whereas EMach is constitute by three components “Machiavellian Tactics”, “Ambivalent Attitudes Toward the Others” and “Social Understanding”. The three teacher’s ratings scales show evidence of construct validity and internal reliability; furthermore ECPRO and EMach show discriminant validity. In addition these findings suggest that teachers are an excellent choice to evaluate this kind of socials behaviors.